Hubungan Pengetahuan Ibu Tentang Tumbuh Kembang Anak dan Keterlibatan Ibu dalam Mengasuh dengan Kemandirian Anak Usia Pra Sekolah - Lestari, Sri Puji; Mendrofa Motuho, Fery Agusman; Ardina, Yenli (Jurnal Smart Keperawatan, 2021)
Tumbuh kembang pada anak terlambat bila tidak mencapai tahap pertumbuhan dan perkembangan yang diharapkan pada umur yang semestinya. Pengetahuan orang tua terutama ibu tentang tumbuh kembang yang memadai memberikan efek terhadap  rata-rata perubahan fisik, intelektual, sosial dan emosional anak dari tumbuh kembang yang normal. Committed in Improving the Health of Indonesia Children yang dirilis Pediatric of Society oleh Ikatan Dokter Anak Indonesia diperkirakan 5-10% anak usia dibawah 5 tahun mengalami keterlambatan umum. Data PAUD Hj. Siti Anisah menunjukkan 3  (60% ) ibu memiliki pengetahuan tentang tumbuh kembang cukup baik, keterlibatan ibu 100% mengasuh sendiri anaknya, kemandirian anak  terdapat 3 (60%) anak mandiri. Tujuan penelitian untuk mengetahui hubungan pengetahuan ibu tentang tumbuh kembang anak dan keterlibatan ibu dalam mengasuh terhadap kemandirian anak usia pra sekolah. Jenis penelitian adalah kuantitatif dengan desain cross sectional, sampel 36 ibu dan anak usia pra sekolah di PAUD Hj. Siti Anisah. Hasil uji Chi square pengetahuan ibu dengan kemandirian anak adalah  p value  0,000 dan  keterlibatan ibu dalam mengasuh terhadap kemandirian anak adalah p value   0,000. Adanya pengetahuan ibu dan keterlibatan ibu dalam mengasuh anak mampu memandirikan anak. Orangtua perlu  menambah pengetahuan tentang tumbuh kembang anak dan terlibat secara optimal dalam pola asuh anak. Kata kunci: pengetahuan; tumbuh kembang; kemandirian,  anak pra sekolah; keterlibatan ibuRELATIONSHIP OF MOTHER'S KNOWLEDGE REGARDING CHILD GROWTH AND MOTHER'S INVOLVEMENT IN PARENTING WITH CHILDREN'S INDEPENDENCE OFPRE-SCHOOL AGE ABSTRACT Growth and development in children is delayed if they do not reach the expected growth and development stages at the age they should be. Parents' knowledge, especially dealing with adequate growth and development, has an effect on the average physical, intellectual, social and emotional changes of children from normal growth and development. Committed to Improving the Health of Indonesian Children released by the Pediatric Society by the Indonesian Pediatrician Association, it is estimated that 5-10% of children under 5 years of age experience general delays. At Hj. Siti Anisah Pre-school, it was showed that 3 (60%) mothers had quite good knowledge about growth and development, 100% involvement of mothers in caring for their children, and 3 (60%) children were independent. The purpose of the study was to determine the relationship between knowledge about child growth and mother's involvement in caring for the independence of pre-school age children. This type of research was quantitative with a cross sectional design, the sample were 36 mothers and pre-school children at Hj. Siti Anisah Pre-school. The results of the Chi square test of mother's knowledge of child independence has p value 0.000 and mother's involvement in caring for children's independence has p value 0.000. The existence of knowledge and involvement of mothers in raising children is able to make children independent. Parents need to increase their knowledge about their child's growth and development and be involved optimally in parenting. Keywords: knowledge; growth and development; independence, pre-school children; mother involvement